Deceptive Design in Cookie Consent Requests: A User-Centered Perspective on Privacy - Tuokkola, Noora; Koskelainen, Tiina; Havinen, Laura; Rousi, Rebekah (RWTH Aachen, 2026)
This study explores how users perceive their privacy in cookie consent requests that feature deceptive patterns, and the role of deceptive design in shaping these perceptions. It proposes a theory-informed analytical framework synthesizing four key factors influencing privacy perceptions: privacy concerns, control over privacy, trust in data collectors, and privacy risks. Using method triangulation – combining user testing, think-aloud protocol, and thematic interviews - the empirical study adopts a user-centered perspective. The findings reveal a predominantly negative influence of deceptive design on privacy perceptions. Although users may have learned to withstand or bypass deceptive patterns, their perceptions were fluid, shaped by the design, context, and personal habits. Overall, users felt their privacy was often compromised, undervalued, and unprotected. This study advances existing knowledge by emphasizing design’s role and offering a synthesized framework capturing the joint influence of perceptual factors on privacy perceptions. It underscores the importance of user experience in privacy evaluations, moving beyond the traditional view of privacy as mere compliance. Moreover, it highlights the paradox of protective mechanisms employing deceptive patterns that compromise user privacy.
Keywords: Cookie consent requests; privacy perceptions; deceptive patterns; deceptive design; privacy by design; fi=Tietojärjestelmätiede|en=Information Systems Science|; fi=Viestintätieteet|en=Communication Studies|